The Effect Of Choking Management Education For Toddlers Aged 1-5 Years On Parents Knowledge - Rafidaini Sazarni Ratiyun; Vellyza Colin; Ida Rahmawati; Lala Nor Safitri; Noza Anita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
Choking is an emergency condition that must be treated quickly, if it takes too long it will result in a lack of oxygen and lead to death due to blockage of the respiratory tract by foreign objects in the form of food, toys, etc. Choking can lead to death due to lack of knowledge of handling choking. The purpose of this study was to determine the effect of education on handling choking in children under five on the knowledge of parents in the working area of ​​the Ratu Agung Health Center, Bengkulu City. This study aims to determine the effect of choking management education on toddlers aged 1-5 years in the working area of ​​Ratu Agung Public Health Center, Bengkulu City. The research design used pre experimental design with a one group pretest posttest design. To determine the number of samples using the Paul Leedy formula with the results obtained are 30 parents who have toddlers aged 1-5 years in the working area of ​​the Ratu Agung Health Center in Bengkulu city. The results of the study: the results of the t-test of two related samples (Paired sample t-test) obtained a value of t = 18.745 with p-value = 0.000 <0.05 significant, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an effect of handling education. choking in toddlers aged 1-5 on the knowledge of parents in the working area of ​​the Ratu Agung Health Center, Bengkulu city. After educating parents in the working area of ​​the Ratu Agung Health Center, Bengkulu city, out of 30 parents, there were 4 parents (13.3%) who had sufficient knowledge, and 26 parents (86.7%) who had good knowledge with a good score. an average of 35.63 (good).